Demographics and Pharmacotherapy in Neurocysticercosis: A hospital Based Study - Shrestha, Resha; Shrestha, Pranaya; Rajbhandari, Pravesh; Acharya, Samir; Chandra, Avinash; Dahal, Sujat; Neupane, Joshan; Gurung, Pritam; Pant, Basant (Annapurna Journal of Health Sciences, 2023)
Introduction: Neurocysticercosis (NCC) is one of the commonest preventable cause of seizure. It is due to development of the larval form of Taenia solium. This disease is endemic in south east Asia including Nepal and has been considered as one of the neglected tropical disease.Methods: All the patients who came to Neurosurgical outpatient department (OPD) of Annapurna Neurological Institute and Allied Sciences (ANIAS) with the diagnosis of NCC with seizure during the study time frame were included in the study. The time frame of the study was January 1st 2017 till December 31st 2018.Results: There were 167 total cases of which 108 (64.7%) were male and 59 (35.3%) were female. Mean age was 27.9 years (SD 13.1 years, range 1 year to 66 years). Frequency of patients were in the age group 20-30 years followed by 10-20 years. In terms of number of lesions, 86% of the patients had single lesion while 14% had multiple lesionsMaximum number of cases had focal seizure with secondary generalization (46%). This was followed by focal seizure (28%). Most common antiepileptics was carbamazepine (51.5%).Mean duration of antiepileptics was 2.5 years (SD 1.47, Range 9 months to 6 years) and recurrence was noted in 7.78% of cases.Conclusion: NCC affects the productive age group with higher proportion being male patient. Single lesion is more prevalent. Proper measures for treatment and prevention of neurocysticercosis is essential and can lead to better control of this condition.